ANALISIS RASIO KEUANGAN DENGAN METODE Z-SCORE (ALTMAN) DAN CAMEL UNTUK MEMPREDIKSI POTENSI KEBANGKRUTAN PADA PERUSAHAAN PERBANKAN YANG LISTING DI BEI - Boby '; Rasuli '; Nur Azlina (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2014)
This research aims to predict the bankruptcy of a company by using the Z Score (Altman) which consists of Working Capital / Total Assets, Retained Earnings / Total assets, Earning before Interest and tax / total assets, and market value of equity / book value of debt . and CAMEL ratio consisting of CAR, ATTM, APB, NPL, PPAPAP, ROA, ROE, NIM, ROA and LDR on banking companies listed on the Stock Exchange 2008-2010. The sample in this study is a banking company that is listed on the Stock Exchange 2008-2010 period as many as 21 companies The results of this research and the test result of the processing by using the Altman Z score obtained 9 predicted bankrupt companies, 10 companies are potentially insolvent (gray area) and 2 healthy company, a total of 21 companies were selected as sample of this. The company is completely bankrupt by year 2 years predictions based on data obtained from the Indonesian Capital Market Directory 2012 only 2 were delisted from the Stock Exchange, the Bank ekomoni Prog Tbk and Bank Executives International Tbk Thus the data processing results obtained show from 9 companies predicted bankrupt, which proved to be bankrupt / mergers are 2 companies with 22.2% accuracy rate. Adjusted R Square shows the value of 0.360. It shows that 36% of bankruptcies are influenced by the determinant variables in the model while the rest (54%) is explained by other variables not included in the model. Thus, it can be seen that there are very many other factors that affect bankruptcies in addition to CAR, ATTM, APB, NPL, PPAPAP, ROA, ROE, NIM, ROA and LDRKeywords: Return on Equity (ROE), Cash Ratio (CR), Debt To Equity Ratio (DER) and Earning Per Share (EPS) The Dividend Payout Ratio (DPR)